Christian Missionaries in Educational and Social Change A Critical Study on the Nagas - Riamei, Lungthuiyang (JOURNAL OF INDIAN EDUCATION, 2010)
The main thrust of the missionaries in India during the nineteenth and early twentieth century was education and spread of Christianity. The paper provides historical overview of Christian missionaries amongst the Nagas. Education at the mission field reflected the dominant old humanist tradition. Christianity has always been associated with education during the colonial period. However, where mission’s education acts as social control, it also tended towards as a social transformation. The article deals about the mssionaries activities in the Indian administered Naga areas. The study brings about how the changes occurred in the Nagas’ society after the coming of the Christian missionaries.